The Outcome of Trauma Patients in the Mixed Semi-closed Intensive Care Unit - Keyal, Niraj Kumar; Yadav, Rajesh; Singh, Alok Kumar; Singh, Amit; Mansuri, Mohammed Islam (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTIONNepal due to its geographical condition, inadequate resuscitation on time, and lack of full-time intensivist in a trauma team is a cause of trauma-related morbidity and mortality.MATERIAL AND METHODSIt was a prospective, descriptive observational cross-sectional study in a level three intensive care unit of National Medical College for six month. All patients >18 years with a history of road traffic accidents, falls, drowning, physical assaults, and self-inflicted violence admitted to the mixed intensive care unit of a tertiary care hospital were included in this study.RESULTSOne hundred and ninety-one patients were included in this study. 152(79.5%) were males and 39(20.4%) were females. A road traffic accident was the most common mode of injury in 166(86.9%) patients. 178(93.1%) patients survived and went home, 10(5.3%) expired, 2(1%) left the hospital against medical advice (LAMA) and 1(0.5%) gave do not resuscitate orders (DNR). The mean days on the mechanical ventilator was 3.39±2.57 days.  Mortality in an intubated patient was 8.6%. Mean LOS in the ICU was 4.28±4.12 days. SOFA and APACHE II scores were a good predictor of outcome, with the SOFA score being the most effective Injury severity score predicted mortality with a sensitivity of 88.9%, a specificity of 22%, with an AUROC curve of 0.543±0.092 with cut off score of 5.5.CONCLUSIONRaising public awareness, and strictly following the traffic rules can help in reducing the incidence of trauma. Trauma team consisting of full-time intensivists should be established to decrease the mortality in the intensive care unit.